PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK ORIFLAME DI KOTA SEMARANG DENGAN MINAT BELI SEBAGAIVARIABEL INTERVENING - Harahap, Latifa Hannum; Khasanah, Imroatul (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze the effect of perceived price, product quality, and brand image on purchasing decisions for Oriflame products in Semarang city with purchase intention as an intervening variable. The population in this study were users who had made transactions or purchased Oriflame products in the city of Semarang and the number of samples used in this study were 120 respondents. In the process of collecting data this research uses a questionnaire method. The analysis technique used is Structural Equation Modeling (SEM) with the help of the AMOS 24.0 analysis tool. The results showed that product quality had a significant effect on purchase intention, price perceptions had a significant effect on purchase intention, brand image had a significant effect on purchase intention, and purchase intention had a significant effect on purchasing decisions.